Analisis Pengelolaan Dana Bantuan Operasional Kesehatan Puskesmas (BOK) terhadap Pelayanan Kesehatan di Wilayah Kerja Dinas Kesehatan Tahun 2023.: ANALISIS PELAKSANAAN TIMBANG TERIMA PASIEN DIRUANG RAWAT INAP UMUM RS TENTARA - Wibowo, Hendry; Nurcihikita, Tiara; Kurniawan, Jefdy (Program Studi Informatika Medis Universitas Muhammadiyah Muara Bungo, 2023)
Background: In order to support the realization of equitable health development, one form of government policy in the health sector is the Special Non-Physical Allocation Fund for the Health Sector, hereinafter referred to as the Non-Physical DAK for the Health Sector. Non-Physical DAK for the Health Sector is a fund allocated to the regions to finance the operations of national priority program activities in the health sector that are regional affairs in order to increase access to and quality of health services in the regions. Implementation and management of non-physical DAK must follow the principles of good governance, namely transparency, effectiveness, efficiency, accountability, and not duplication with other funding sources. In its implementation, DAK's Non-Physical Health Sector refers to Minister of Finance Regulation No. 204 of 2022. DAK funds consist of BOK, Maternity Guarantee, Community Health Center Accreditation, and Drug and Food Supervision. Research Methods: This research is comparative, where this research focuses on comparing the realization of the management analysis of Health Operational Assistance (BOK) funds taken from the Merangin Health Office object with Minister of Finance Regulation Number 204 of 2022. This research uses a qualitative method; according to Shiddiq and Choiri (2019), qualitative research is research that produces findings that cannot be achieved using statistical procedures or quantitative methods. There were five informants in this study. This research was carried out in July–August 2023 at the Merangin Health Service. Research Results: From the planning aspect, it can be explained that the management of BOK funds at the Merangin Health Office is 100% in accordance with PMK regulations No. 204 of 2022, namely starting from the allocation of BOK seen from the plan for carrying out activities by attaching a letter submitting SPM GU to BPKAD Merangin, which is based on the number of residents around the work area of each health center, conditions around the work area of the health center, and the proposed program. The next stage is planning and preparing the RUK and RPK at each community health center, which is also in accordance with PMK regulation No. 204 of 2022. Conclusion: Planning in the financial management of the BOK for each health center starts with the proposed activity plan (RUK) made by the health center, which then becomes an activity implementation plan (RPK) through approval from a meeting with the Merangin Health Office and the BOK and RPK management team as a condition for allocating BOK funds.